Haematological and Biochemical Studies on some Ruminants - LC Chuku; AA Uwakwe (Journal of Applied Sciences and Environmental Management, 2013)
Haematological studies of ruminant vertebrates (cow, sheep and goat) present one acceptable method of understanding the ecological biochemical and physiological relationship between lower and higher vertebrate animals like man. Haematological/Biochemical studies were carried out on blood from the vertebrate ruminants: Goat (Capra hircus-L), sheep (Ovis Aries dolrchra), cattle (Bos Taurus) and human (Homo sapiens) as control, indicated that; Electrophoretically goat blood revealed three different Hb polymorphic types: HbAA (45%), HbAS (50%) and HbSS (5%). Only the ‘O’ Rh blood group was observed in all cases, and GST values of 4.05-6.30 I.U were obtained on the other hand. Cow Hb electrophoresis produced two patterns corresponding to the human HbAA and HbAS types. Only the ‘O’ Rh- blood group was obtained in all cases and GST values of 2.85-5.02 I.U were obtained, while sheep blood produced only the HbAA-type, only the ‘O’ blood group was identified in all case. GST activity values were in the range of 3.05-4.52 I.U. These results could point to definite haematological and biochemical similarities in man and ruminants and thus serves as a springboard for further genetic studies using lower vertebrates research models.